2015
DOI: 10.1007/s13346-015-0228-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved immunogenicity of individual influenza vaccine components delivered with a novel dissolving microneedle patch stable at room temperature

Abstract: Prevention of seasonal influenza epidemics and pandemics relies on widespread vaccination coverage to induce protective immunity. In addition to a good antigenic match with the circulating viruses, the effectiveness of individual strains represented in the trivalent vaccines depends on their immunogenicity. In this study we evaluated the immunogenicity of H1N1, H3N2 and B seasonal influenza virus vaccine strains delivered individually with a novel dissolving microneedle patch and the stability of this formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 58 publications
6
74
0
Order By: Relevance
“…MNPs were prepared by a two-step micro-molding process described previously [34]. Briefly, TT monobulk was first concentrated ten-fold using 10 kDa MWCO spin filters (EMD Millipore, Billerica, MA).…”
Section: Fabrication Of Mnps For Encapsulation Of Tetanus Toxoid Vaccinementioning
confidence: 99%
“…MNPs were prepared by a two-step micro-molding process described previously [34]. Briefly, TT monobulk was first concentrated ten-fold using 10 kDa MWCO spin filters (EMD Millipore, Billerica, MA).…”
Section: Fabrication Of Mnps For Encapsulation Of Tetanus Toxoid Vaccinementioning
confidence: 99%
“…Previous studies have proved that a metal MN patch coated with WVP or SV vaccines induced antibody responses higher than or equivalent to those induced by SC administration in animals [17]. A dissolving MN using a hydrophilic biopolymer has been developed because it need no disposal, could be selfadministered, would have good stability and shelf life [18][19][20][21][22]. Previous studies have demonstrated that TD vaccination in combination with SV vaccines prepared from seasonal influenza viruses using a dissolving biopolymer needle induced higher antibody responses than SC vaccination in humans [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a dextran-based influenza vaccine-loaded DMN system [25] or hyaluronic acid-based microneedle patch system [48] demonstrated lower stability compared to our system when samples were stored at ambient (25ºC) or accelerated (40ºC) temperatures and tested using SRID or in vivo. However, a monovalent influenza vaccine demonstrated promising stability at 25ºC for 3 months [32] and using in-house ELISA-based assays, other formulations have been suggested for stabilizing influenza vaccines in microneedle structures [49] Other efforts that incorporated TIV onto transcutaneous patches were also less successful at elevated temperatures; however the relative stability of the H1N1 compared to H3N2 antigens was also observed in this study [50].…”
Section: Accepted M Manuscriptmentioning
confidence: 71%
“…Successful skin transfection by live virus vaccines delivered by these DMN patches confirms that virus is well preserved in the microneedles, that microneedles penetrate the skin and that skin cells were successfully transfected and produced -galactosidase. Similar to other microneedle technologies [32,55,56] it is unlikely that 100% of the vaccine was delivered into the skin, particularly when the vaccine is distributed throughout the microneedle. This suggests that even greater dose-sparing may have been achieved in this mouse model due to sub-optimal vaccine delivery efficiency.…”
mentioning
confidence: 99%